EFEK PAPARAN GLUKOSA KONSENTRASI TINGGI TERHADAP PENINGKATKAN AKTIVITAS ISOZIM PROTEIN KINASE C (PKC)-ALPHA PADA KULTUR SEL STROMA PROSTAT - Purnomo, Basuki B; Widharse, I Wayan; Aulani’am, Aulani’am (Indonesian Journal of Urology, 2009)
OBJECTIVE: To prove that glucose treatment in human prostatic stromal cells (HPSC) culture would increase PKC alpha isozyme activity. MaterialS & Methods: Primary cultures of HPSC were obtained from patients with bladder outlet obstruction caused by benign prostatic enlargement. The effects of various concentrations of glucose (5, 10, 15, 20, 25, 30, 35 micro-Mol) on PKC-alpha isozyme activity were examined quantitatively by spectrophotometry methods. ResultS: Spectrophotometry analysis, which is used to assess isozyme activity quantitatively, showed that exposures to various doses of glucose resulted in increased isozyme activity. The increment of activity is linear with the increment of glucose dose. There is a strong correlation between glucose doses and PKC-alpha activity, with R2 = 0,91. Conclusion: At different concentrations glucose increases PKC-alpha isozyme activity of HPSC.